Interest rate, debt, distribution and growth: A post-Keynesian model in a coherent stock-flow monetary framework - Liao, Shuiqiang (Université d'Ottawa | University of Ottawa, 2005)
In this paper, the author attempts to build a more complete Kaleckian distribution and growth model based on Lavoie's (1995) "Minsky-Steindl-model", which was further elaborated in Hein (1999, 2005). It extends the analysis of the impact of variations in